DESIGN AND IMPLEMENT LARAVEL FRAMEWORK BASED WEBSITE FOR NATIONAL ELEMENTARY SCHOOL 1 TEGALPINGEN USING AGILE METHOD - Vito Raditya Fauzan; M. Alfian Maulana Al-Azhar; Nisrina Eka Salsabila (Institute of Computer Science (IOCS), 2022)
The need for information is important for agencies such as schools that need media and information facilities to provide for the teachers, students, parents, and the public. However, there are still many problems because the media used to convey the information is still limited and does not cover all people who need it. The website that is built can display information that usually exists on the school website, namely profiles, vision and mission, news, and others. In addition, this website can also display data such as student and teacher directories. Student and teacher data will be briefly displayed on the website using tables so that the layout of the directory is neat. The website will have features such as a guest book, comments on the news content section so that there is interaction between the user and the system. With this website, schools can convey information widely. Furthermore, this website also provides news about new student admissions, so that the general public if anyone wants to register a child or sibling can view the information on the school's website, with the aim of making it easier for prospective applicants. Therefore, we wants to design a dynamic website for the National Elementary School 1 Tegalpingen which can later be used as a medium for publishing all information related to the school. With this website, it is hoped that it will increase the public's interest to study at the National Elementary School 1 Tegalpingen.